The Australian Byrrhinae (Coleoptera: Byrrhidae) with descriptions of new genera and species - Lawrence, John F.; Slipinski, Adam; Jäger, Olaf; Pütz, Andreas (Zootaxa, 2013)
The generic classification of the Australian Byrrhinae is revised and the following new genera are described: Notolioon gen. n., Nothochaetes gen. n., Idiothrix gen. n., Akidomorychus gen. n., Brachybyrrhulus gen. n. and Pseudomorychus gen. n. A key is provided for the genera of Australian Byrrhidae. The following new combinations are proposed: Notolioon atronitens (Lea 1920) comb. n., N. bryophagus (Lea 1907) comb. n., N. carissimus (Lea 1907). comb. n., N. dives (Lea 1907) comb. n., N. gemmatus (Lea 1920) comb. n., N. globosus (Wilson 1921) comb. n., N. griffithi (Lea 1907) comb. n., N. maculatipes (Lea 1920) comb. n., N. multicolor (Lea 1907) comb. n., N. nodipennis (Lea 1920) comb. n., N. simplicicornis (Lea 1907) comb. n., N. viridinitens (Lea (1920). comb. n., Nothochaetes fasciculatus (Lea 1920) comb. n., Idiothrix carinaticeps (Lea 1920) comb. n., Akidomorychus comatus (Oke 1932) comb. n., A. polychromus (Lea 1920) comb. n., A. raucus (Blackburn 1891) comb. n., A. venustus (Wilson 1921) comb. n., Brachybyrrhulus discicollis (Lea 1920) comb. n., Pseudomorychus torrensensis (Blackburn 1889) comb. n., P. mixtus (Lea 1907) comb. n. The following new species are described: Notolioon cardamine sp. n., Nothochaetes howensis sp. n. and Brachybyrrhulus malleecola sp. n.